The Contribution of Career Level in The Work-life Balance of Muslimah's Entrepreneur - Novi Febriyanti; A. Fikri Amiruddin Ihsani (Raheema, 2021)
A career woman has a good career development or career level in her work, it will have a contribution in work-life balance, and work-life balance is also one of the factors supporting the success of Muslimah’s entrepreneurs. The purpose of this study was to know and have a clear picture of the contribution of career levels in Muslimah’s entrepreneurs and the contribution of work-life balance in Muslimah’s entrepreneurs. This research method uses descriptive qualitative with a field research approach. Field research is research that emphasizes the practice in the field. In this study the author focuses on the results of data collection obtained directly from the informants and the specified sources. The results of this study prove that career level with work-life balance in Muslimah's entrepreneur shows results that are supportive meaning that the higher the career path the higher the work-life balance in Muslimah's entrepreneur. Vice versa, the lower the career path, the lower the work-life balance of Muslimah’s entrepreneurs. Supporting factors at the career level are education, guide and sponsorship, loyalty to business organizations as well as social flexibility and relationships between employee, assessment and evaluation and achievement or appreciation at work. While the supporting factors in work-life balance are working hours, personality characteristics, emotional intelligence and psychological well-being.